Evolution of the northern Turkana Depression (East African Rift System, Kenya) during the Cenozoic rifting: New insights from the Ekitale Basin (28‐25.5 Ma). (21st October 2018) - Ragon, Théa; Nutz, Alexis; Schuster, Mathieu; Ghienne, Jean‐Francois; Ruffet, Gilles; Rubino, Jean‐Loup
Abstract : Two sedimentary basins are identified in the Turkana Depression (East African Rift System, Kenya). One of them, the Ekitale Basin, is presented in detail. Located on the western rift shoulder of the northern Turkana Depression, the preserved portion of the Ekitale Basin is 3–5‐km wide and bordered by N40°–50° normal faults. These normal faults were inherited from the reactivation of pre‐existing basement structures. The Ekitale Basin is filled by the 75‐m‐thick Topernawi Formation. The lower portion of the formation provides evidence that the basin was occupied by a lake, bordered by alluvial fans, and into which river‐derived turbiditic complexes were deposited. The upper portion is comprised of pyroclastic deposits, originating from volcanic activity, and interbedded with fluvial deposits emplaced during periods of volcanic quiescence. The Ekitale Basin opened just after 28 Ma and was abandoned prior to 25 Ma, placing it after the deposition of the Oligocene Traps ( ca . 33.9–27 Ma) and prior to the rift climax (after 14 Ma). This syn‐rift basin largely impacts our understanding of the Cenozoic rift evolution in the Turkana Depression. It helps to identify, for the first time, the first pulse of extension of the Cenozoic rifting, revealing a two‐step rifting scenario for the northern Turkana Depression. The Ekitale Basin, and analogous syn‐rift basins, is believed to have developed from the reactivation of pre‐existing structures during a period of extension marked by low differential stress and a low amount of extension.